On the measurement of sub-surface residual stresses in SS 304L welds by dry ring core technique. (August 2017) - Giri, A.; Mahapatra, M.M.
Highlights: Residual stresses in SS 304L welds investigated by dry ring core technique. A hollow trepanning tool was developed to minimize machining stress. Calibration test of rosettes was conducted to validate FE model. Transverse residual stresses were maximum at root side of weld. Longitudinal residual stresses were maximum at top side of weld. Abstract: Sub surface residual stresses in thick multi-pass stainless steel butt welded joints were measured by dry ring core technique. To accomplish the task of dry ring coring, special tools were developed such that machining induced stresses were negligible. Established equations, analytical methods and regression correlations were used in the measurement. A database of mathematical relations of residual stress values was also developed using the response surface methodology. A 3-D finite element (FE) model was used to prepare the residual stress field data at the different stress ratios at various depths of the welded joints. Further, this data was used to develop the regression equations as well as to determine the calibration coefficients.